The bureaucracy trap - Andina-Díaz, Ascensión; Feri, Francesco; Meléndez-Jiménez, Miguel Ángel (Elsevier, 2023)
We study the incentives of political parties to institute reforms that improve bureaucratic quality and increase the ability of governments to implement policy change. We consider a context of dynamic elections where current rigidities do not permit large changes in policies. We show that reforms in which a sufficient share of benefits are experienced late in time will never be implemented if parties are patient enough.
Keywords: Política - Reforma; Political alternation; Institutional reform; Bureaucracy trap